Analysis of Woorkload and Comitment of Midwives to Patients in the Maternal and Child Health Clinic at the Health Center in Mojosari Sub District - Indarsih; Suprapto, Sentot Imam; Siyoto, Sandu (Journal for Research in Public Health, 2020)
Service quality is not due to power quality factors but also because of the high workload received by health workers (Ilyas 2011) besides that an employee is required to have commitment to the organization, high commitment will have an impact on improving the career of the employee itself (Sopiah 2010),The purpose of the study was to determine the effect of workload and affective commitment, ongoing commitment and normative commitment of midwives at the Health mother and child in Mojosari sub-district. The research method used was an analytical survey with the approach used was cross sectional research conducted in November 2018 at the health and child Poly Health Center in Mojosari Subdistrict with a sample of 111 respondents for vanable independent and 37 respondents for independent variables for dependent variables were patient satisfaction, and varic independent is an ongoing commitment affective commitment and normative commitment to collecting data using a statistical test questionnaire using logistic regression with a- 0,005. The results showed that the high workload of midwives was 17 prang (42.2%), the workload of midwives was low 20 respondents (43.3%), high affective commitment 21 respondents (56.8%) continued high commitment 22 respondents (59.4%) high normative commitment 189 respondents (48.6%), while for dependent variables that is patient satisfaction obtained by patients who expressed satisfaction 19 respondents (5 1.4%) and who expressed dissatisfaction 18 respondents (48.6%) the results of the study found variable workload (p 0.001) Affective Commitment variable (p-0.001) Continuous commitment (p 0.001) normative variable (p-0.002) so that the independent variable has significant effect on patient satisfaction but high workload variables are more at risk of increasing patient satisfaction with grades exp B Odd ratio (OR) 142,440 the result of the study that the burden of high workloads at risk of increasing disssafacation in patient”s as well as midwives with middle commitment also at risk of increasing dissatifacation in patient’s. The conclusion There was effect workload and midewife’s commitment to patient satisfacation at maternal and child health at the Mojosari health center